Junior classics, 3 (The call of the wild) - London, Jack.; Melville, Herman; Andersen, Hans Christian; Orwell, George (b, 2016)
The Junior Classics series, comprising twenty titles, introduces young readers to literary masterpieces by celebrated authors, ranging from Charles Dickens and R.L. Stevenson to Louisa M. Alcott and H.G. Wells. The all-time popular novels packed with colourful illustrations bring alive the lovable characters and can keep children entertained for hours. Each book in the series has a collection of four stories from diverse genres and by different writers, which makes reading a lot of fun. Thoughtfully abridged and told in simple language, this engaging series will kindle the love for reading in children. This treasure trove of eighty stories, ranging from adventure, fantasy, satire to mystery and romance, will be a welcome addition to any child$1 (Bs personal library.s
Keywords: Moby Dick or the Whale; The Little Mermaid; Animal Farm